SKEPTISME TERHADAP AGAMA DALAM FILSAFAT DAVID HUME ( 1711-1776) - Saidul Amin (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2010)
History of Western civilization can not be separated from philosophy and religion. At first the philosophy was born as a force infantry to break thought the dogmas and ideas of superstition that has been ingrained in the public body. Then came the religion as a "golden bridge" toward the ultimate truth "via a toll road" called revelation. But the two do not always go hand in hand. There are times when utilizing the philosophy of religion, but not infrequently refuse philosophy of religion, either vulgar or skeptical as performed by David Hume who argue that religion is superstition and only adikudrati busy talking about aspects that are far away from human observation. This article will discuss these the issues